Sistem Untuk Deteksi Penyakit Stroke Menggunakan Metode Analytical Hierarchy Process dan Weighted Product - Ibrahim Kusuma; Arief Andy Soebroto; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Stroke is a disease caused by blockage of blood in the brain or rupture of blood vessels in the brain, resulting in brain nerve palsy. Stroke is one type of diseases that kill high enough third after heart disease and cancer in developed countries. The data of East Asian Medical Information Center (SEAMIC) is the highest in Indonesia. This causes the disease to be wary of. Doctors sometimes have difficulty to perform stroke disease detection due to a semi-structured problem. These constraints can be overcome by a system that is Decision Support System using the method of Analytical Hierarchy Process and Weighted Product. Analytical Hierarchy Process method is used to find the priority weight and Weighted Product method used for decision making and ranking. The result of system functionality testing is 100%. As for the system accuracy testing has an accuracy of 73.8%.